Hubungan Usia Dan Paritas Dengan Kejadian Anemia Pada Ibu Hamil di Puskesmas Takalala Kabupaten Soppeng - Afriani Afriani; Wirawati Amin; Theresia Limbong; Apnitasari Apnitasari (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
The Maternal Mortality Rate (MMR) increased from 288 to 359 per 100,000 live births. Bleeding is the main cause of maternal death. One of the causes of bleeding is anemia during pregnancy. The purpose of the study was to determine the relationship between age and parity with the incidence of anemia in pregnant women. The research method is an analytic survey with a cross sectional approach and sampling using purposive sampling with a total sample of 42 in accordance with the criteria set by the researcher. Secondary data collection using a checklist sheet, the time of the study is April – May 2021, the statistical test used is the Chis - quare test with the results of p = 0.002 < 0.05 where there is a relationship between Age and Parity with the incidence of anemia in pregnant women at the Puskesmas Takalala Kab. Soppeng.